Colisão e chaveamento de solitons em fibras ópticas especiais - Feitosa, Carlos Alberto Carneiro (1995)
The propagation and switching of solitons in nonlinear optical fibers and devices have been investigated with the split-step Fourier method and variational method. Our results suggests that solitons are good candidates for transmission and switching in optical fiber devises at high bit rates. The study of soliton stability also shows that high order multiphoton susceptibility plays an important role in the soliton stability.